Estudio de factibilidad para la creación de un paradero turístico en el sector de puembo cantón La Maná, año 2013. Quevedo - Lalvay Casillas, Nancy Jacqueline (2013)
This research was conducted in the Canton La Maná which has 42216 inhabitants consisted of market research, technical, organizational, economic, and financial evaluation projected 5-year term in order to give the investor a tool support for the creation of a tourism sector whereabouts Puembo, same as encourage tourists who come to dislike varied dishes of the region. The feasibility study conducted in this research project envisioned that the potential demand that supports the creation of a tourism sector whereabouts Puembo is 92% of a total of 396 respondents, which means there is wide acceptance important for this type of business. The investment project provides a total of $ 53387,70 for the full implementation of this project is required to make this investment to obtain a loan of $ 53387,70 in the CFN is needed the same within a period of 60 months will be paid in full ………..